Gender‐Affirming Hormone Treatment Decreases Bone Turnover in Transwomen and Older Transmen - Vlot, Mariska C (J Bone Miner Res, 2019)
Sex steroids play a key role in bone turnover and preserving BMD; hence, gender‐affirming hormone treatment (HT) in transgender people affects bone metabolism. Most studies have looked into the effect of HT on changes in BMD; however, they do not provide insights into changes in bone metabolism caused by HT. This study investigated changes in bone turnover markers (BTMs) and sclerostin, as well as their correlations with change in BMD in transwomen and transmen during the first year of HT. Transwomen received estradiol and antiandrogens; transmen received testosterone. Sclerostin; P1NP; alkaline phosphatase (ALP); CTx; and BMD of the total hip, the femoral neck, and the lumbar spine were evaluated at baseline and after 1 year of HT. There were 121 transwomen (median age 30 years, interquartile range [IQR] 24 to 41 years) and 132 transmen (median age 24 years, IQR 21 to 33 years) included in the study. In transwomen, ALP decreased in 19% (95% CI, –21 to–16), CTx in 11% (95% CI, –18 to–4), and sclerostin in 8% (95%CI, –13 to–4) of study participants after 1 year of HT. In contrast, in transmen P1NP, ALP, and sclerostin increased in 33% (95% CI, 24 to 42), 16% (95% CI, 12 to 20), and 15% (95% CI, 10 to 20) of study participants, respectively, after 1 year of HT. No age differences were seen in transwomen, whereas in transmen aged ≥50 years a decrease in all BTMs was found in contrast with the other age groups. These transmen had low estrogen concentration at the start of HT based on their postmenopausal state before the start of HT; their estradiol concentrations increased during testosterone treatment. Changes in BTMs and BMD were weakly correlated (correlation coefficient all <0.30). To conclude, 1 year of HT resulted in decreased bone turnover in transwomen and older transmen, whereas it increased in younger transmen. The decrease in bone resorption in older transmen shows the importance of estrogen as a key regulator of bone turnover. © 2019 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals, Inc.